Strategies to Increase Organizational Commitment at the Bogor City Environmental Services Thru Programs to Strengthen Perceived Organizational Support, Job Satisfaction and Work Motivation - Irawan, Idham; Yusnita, Nancy; Sunaryo, Widodo (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to identify strategies for increasing organizational commitment thru programs that strengthen perceived organizational support, job satisfaction, and work motivation. The research method uses a quantitative approach with a sample of 93 respondents. The respondents are civil servants holding non-managerial positions at the Bogor City Environmental Agency. The data was processed using Structural Equation Modeling (SEM). The research results indicate that perceived organizational support has a direct negative and insignificant impact on organizational commitment, but it has a positive and significant impact on job satisfaction and work motivation as mediating variables. Perceived organizational support was found to indirectly influence organizational commitment thru job satisfaction. However, perceived organizational support was not found to indirectly influence organizational commitment thru work motivation. The findings of this study confirm that perceived organizational support does not directly increase organizational commitment, but plays an important role thru increased job satisfaction. Conversely, work motivation is not an effective mediating path, so job satisfaction emerges as the main mechanism explaining how perceived organizational support can strengthen employes' commitment to the organization